An Augmented Reality Platform inside PURESAFE project - Martínez, Héctor; Laukkanen, Seppo (Journal on Interactive Systems, 2014)
This paper presents the results of a three-year research project inside PURESAFE project. PURESAFE contains 15 research projects and aims to enhance the life-cycle management of facilities emitting ionizing radiation. The research project presented in this paper focuses in Augmented Reality solutions for maintenance purposes. The outcome of the research project is a new platform containing an Augmented Reality engine and an authoring tool for the creation of Augmented Reality applications for maintenance in large scientific facilities emitting ionizing radiation. The platform has been developed and tested in real conditions.